PEMBERDAYAAN IBU RUMAH TANGGA KELURAHAN TOBEK GODANG DIVERSIFIKASI OLAHAN IKAN AIR KOLAM - Wiyati, Rita; Salmiah, Neneng; Waldelmi, Idel; Hartati, Adilla; Hikmah, Wildatul (Komunitas Manajemen Kompetitif, 2023)
The COVID-19 pandemic has an impact on all fields, from economics, social, pilotik, culture, to education. Many things are highlighted negatively with the current outbreak, but there are still many opportunities for us who are able to see and innovate to take advantage of them, including residents of the Housewives of RT 08 Tobek Godang sub-district, who are partners in Community Service activities, who have been housewives who only rely on sources of income from their husbands and housewives' activities are only social gathering and recitation, so during the current pandemic they are thinking of taking advantage of the opportunities that exist. The purpose of holding PKM for this community is to make processed freshwater fish that can be processed into fish ball products, packaging and can help increase family income in addition to motivating partners to be able to have the intention to be entrepreneurial and have a good business plan. The method used is to provide counseling about the importance of entrepreneurship and training to market products in good packaging. The program implementation methods that will be carried out are: business management training, fish ball processing packaging training, . All of these methods are an integral part of this PKM program. The results of the implementation of community service carried out on Sunday, May 22, 2022 and Friday, May 27, 2022, that housewives in the RT 08 area in the Tobek Godang village began to understand that the packaging of a product is very important, especially attractiveness in marketing the product. Keywords: Business Management, marketing, packaging